PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. ASURANSI BUMIDA BUMIPUTERA MUDA CABANG AMANDO - Noldison Lotje; Sontje M. Sumayku; Sofia A. P Sambul (Universitas Sam Ratulangi, 2017)
Background of this research conducted at PT. Insurance BUMIDABumiputera Muda Manado Branch. In doing this research used quantitativemethod, while data collection was done by interview and ask kuisoner toemployees at PT. Insurance BUMIDA Bumiputera Muda Manado Branch.Population in this research is all employees at PT. Insurance BUMIDABumiputera Muda Manado Branch. While the sample is determined by using theCensus method, which is the collection of data covering all elements / members ofthe population investigated. From the result of validity and reliability test, it isknown that the result obtained is bigger than the specified value validity (0,3) andreliability (0,6) so it can be said the data is valid and the instrument is reliable.From the results of simple regression analysis known R.Square value of 0.753influence of Leadership Style on Employee Performance at PT. BUMIDAInsurance Bumiputera Muda Manado Branch, while the is influenced by otherfactors outside the free factor studied. From the results of partial testing can beconcluded that the factor of Leadership Style has an influence on Employeeperformance at PT. BUMIDA Insurance Bumiputera Muda Manado Branchproved true because the variable Leadership Style hast count of 7,415. After doingthe research it can be concluded that the style of leadership has a significant effecton Employee Performance at PT. Insurance BUMIDA Bumiputera Muda ManadoBranch.Keywords: Leadership Style and Employee Performance